Toll-like Receptor 4 Modulation as a Strategy to Treat Sepsis - X. Wittebole; D. Castanares-Zapatero; P. F. Laterre (Mediators of Inflammation)
Despite a decrease in mortality over the last decade, sepsis remains the tenth leading causes of death in western countries and one of the most common cause of death in intensive care units. The recent discovery of Toll-like receptors and their downstream signalling pathways allowed us to better understand the pathophysiology of sepsis-related disorders. Particular attention has been paid to Toll-like receptor 4, the receptor for Gram-negative bacteria outer membrane lipopolysaccharide or endotoxin. Since most of the clinical trial targeting single inflammatory cytokine in the treatment of sepsis failed, therapeutic targeting of Toll-like receptor 4, because of its central role, looks promising. The purpose of this paper is to focus on the recent data of various drugs targeting TLR4 expression and pathway and their potential role as adjunctive therapy in severe sepsis and septic shock.